THE VISION AND IMPLEMENTATION OF INTELLIGENT SECURITY SYSTEM - BUROV, EUGENE; ZHOVNIR, YURIY; ZAKHARYA, OLEH (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The implementation of artificial intelligence in all areas of information technology promises significant productivity improvements, particularly in security systems. In the context of modern threats and a high level of unpredictability, security systems are an environment where the use of intelligent technologies can provide maximum efficiency. Intelligent security systems not only respond to incidents but also predict their development, enabling proactive actions and risk minimization. Such systems represent a new approach to security, focusing on situational awareness and real-time data processing. This article presents approaches to the implementation of an intelligent security system capable of detecting and analyzing situations, using the collected information to make operational decisions. The core of the system is based on the General Formal Ontology, which allows for the creation of a unified model of concepts and objects, ensuring data consistency and interpretability. This approach simplifies the integration of the system with other components and expands its application capabilities. The initial version of the intelligent security system includes two key modules: a front-end for user interaction and a back-end that handles data processing and system management. These components perform essential functions such as access control and surveillance, allowing for effective management of security processes in real-time. A vital part of the system is the knowledge base, which contains scenarios of typical incidents and algorithms for handling them, enhancing the responsiveness and reducing the number of false alerts. The system provides not only monitoring but also analytics, optimizing risk management processes. The implementation of such solutions opens new perspectives for the integration of AI into security systems, enhancing their efficiency. The proposed architecture allows for the development and scaling of the system in accordance with new requirements and challenges faced by modern infrastructures. This research represents a significant step towards the creation of next-generation security solutions, focused on high performance, reliability, and situational awareness.